PENGARUH RASIO LIKUIDITAS DI UKUR DENGAN CURRENT RATIO (CR), QUICK RATIO (QR) DAN RASIO PROFITABILITAS DI UKUR DENGAN RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE) TERHADAP RETURN SAHAM DI PERUSAHAAN OTOMOTIF PERIODE 2012-2014 DI BURSA EFEK INDONESIA ( - brahmayanti, Ida Ayu Sri; Zunaini, Elis (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2016)
In running the business of each company, especially companies that go publicrequire substantial capital. Therefore, the owner is directed to the capital markets toattract investors. Investors tend to choose stocks that can provide maximum benefit.This study aims to know the effect of the current ratio (CR), quick ratio (QR), return onassets (ROA) and return on equity (ROE), simultaneously and partially on stock returnsautomotive companies that go public in Indonesia Stock Exchange period 2012 - 2014.the research type used is explanatory, multiple linear regression, correlation coefficientanalysis, coefficient of determination analysis, F test and T. dependent variable stockreturns and independent variables CR, QR, ROA and ROE. Simultaneously, the analysisshows that CR, QR, ROA and ROE have influence on stock returns with a valueanalysis regression coefficient consecutive y = 0.139 + 0.004 Xâ‚ - 0.768 Xâ‚‚ + 0.009 Xâ‚ƒ+ 0.008 Xâ‚„ which means that the variable CR, ROA, and ROE has a positive influenceon stock returns. whereas for variable QR negative effect. Partial correlation coefficient(r) respectively for 0.127619; 0.253654; 0.213551; 0.050402 shows the relationshipbetween independent variables and the dependent variable is positive as it approaches +1. This means that research is able to sample that can be applied also to the population.The coefficient of determination (R Â²) of 0.378 = 37.8% of adjusted R square of 0.143 =14.3% means that all four independent variables have an influence of 14.3% and 85.7%influenced by other factors. Significance test (t test) for each variable of CR = 0642,0946 = ROE, ROA = 0.926 and QR = 0.500, which means no effect on stock returnsbecause of its significance> 0.05. meurut simultaneous test also showed that 0.292 <ofwhich 4.12. In addition it also shows the significance of greater value than alpha withalpha 0.05 then Hâ‚€ acceptable means independent variable has no effect on thedependent variable significantly with 95% confidence level. So it can be concluded thatthe variable (X) is CR, QR, ROA and ROE do not significantly affect stock return (Y).Keywords: (CR, QR, ROA, and ROE) (stock return)